Effects of X-irradiation on rat hair follicles - Molinari de Rey, Beatriz L.; Bernaola, Omar Alberto; Galmarini, D.; Autorino, P. (Taylor & Francis Ltd., 1986)
Fil: Molinari de Rey, Beatriz L. Comisión Nacional de Energía Atómica; Argentina